Analisa Suseptibilitas Magnetik Lindi (Leachate) Tempat Pembuangan Akhir (TPA) Sampah Kota Kendari - La Ode Ngkoimani; Jahidin .; Nur Ashira (Jurnal Aplikasi Fisika, 2016)
Research on magnetic susceptibility analysis of leachate of solid waste of Kendari in two leachate  in  order  to  determine  the  value  of  magnetic  susceptibility  and  determine  the magnetic minerals contained in the leachate (leachate). Measurements in this study consisted of measurement of magnetic susceptibility. The results of measurements of magnetic susceptibility values show that the range of values of magnetic susceptibility at low frequencies are mixed. Value of magnetic susceptibility of leachate (leachate) ranging from 3.7 x 10-8m3kg-1  up to 38 x 10-8m3kg-1. Based on the value of the dominant magnetic mineral in each pool of the final disposal (landfill) Municipal Solid Waste Kendari is suspected to have any kind of magnetic minerals hematite (Fe2O3) and Pyrite (FeS2)